2000
DOI: 10.1159/000021358
|View full text |Cite
|
Sign up to set email alerts
|

Der Wirkungsmechanismus von wässrigem Torfextrakt auf die spontane kontraktile Aktivität der glatten Muskulatur

Abstract: The Effect of Aqueous Peat Extract on the Spontaneous Contractile Activity of Smooth MusclesBackground:There are reports in the literature about the effects of peat and its products on spontaneous contractile activity (SCA) of smooth muscles. In our earlier work we showed that the aqueous peat extract is a stimulus for SCA of smooth muscle fibres. After longstanding (4–5 h) influence from aqueous peat extract, a selfblocking effect of these influences can be observed. The mechanism of action could not be deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 0 publications
0
4
0
3
Order By: Relevance
“…3, below). These effects are analogous both in character and in mechanism of action to the effect of the water peat extract on SCA of SMS [2]. The only difference is the magnitude of the contractile activity, which is several times higher for water peat extract.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…3, below). These effects are analogous both in character and in mechanism of action to the effect of the water peat extract on SCA of SMS [2]. The only difference is the magnitude of the contractile activity, which is several times higher for water peat extract.…”
Section: Discussionmentioning
confidence: 65%
“…In earlier studies of ours we have demonstrated that the water peat extract (WPE) possesses agonistic properties with respect to the a 2 −adrenergic− and D 2 −dopamine receptors [2]. These ef− fects of water peat extract are due to the water−soluble compo− nents of the humic acids contained in peat [4].…”
Section: Abstract Mud´peat´curative Mud´humic Substances´a 2 −Adrenementioning
confidence: 80%
See 2 more Smart Citations
“…In unseren bisherigen Arbeiten konnten wir zeigen, dass wässeriger Torfextrakt (WTE) eine anregende Wirkung auf die spontane kontraktile Aktivität (SKA) glatter Muskelstreifen (GMS) besitzt [4,5]. In unseren bisherigen Arbeiten konnten wir zeigen, dass wässeriger Torfextrakt (WTE) eine anregende Wirkung auf die spontane kontraktile Aktivität (SKA) glatter Muskelstreifen (GMS) besitzt [4,5].…”
unclassified